(untitled) (Canadian Journal of Native Studies, 2026)
Since the colonisation of their land in 1534, Canada’s Indigenous population has suffered adverse health outcomes of colossal magnitude. The intergenerational impacts of such events persist in the current day, with contemporary Indigenous Canadians experiencing extreme health disparities in comparison with their non-Indigenous counterparts. Consequently, Indigenous Canadians are targeted by numerous health interventions which, despite claiming to improve health outcomes, often see no benefit and more concerningly, reinforce negative health behaviours and spur discrimination, thereby propagating Canada’s neo-colonial political agenda. This narrative essay employs Patricia Hill Collins’ matrix of domination to explore the power relations underpinning such health interventions and provides recommendations for reforms within Canada’s healthcare system. Although Indigenous activism and sovereignty are occurring within the hegemonic and interpersonal domains of power, the studies analysed herein reveal that many health interventions fail to yield positive results due to persistent racist legislations and establishments within the structural and disciplinary domains of power. As such, nationwide political reforms must move beyond encouraging simple ‘partnerships’ between Indigenous and Euro-Canadian healthcare officials, to foster true Indigenous healthcare leadership and autonomy.